Evidence‐based management of vitiligo: summary of a Cochrane systematic review. (25th March 2016) - Whitton, M.; Pinart, M.; Batchelor, J.M.; Leonardi‐Bee, J.; Gonzalez, U.; Jiyad, Z.; Eleftheriadou, V.; Ezzedine, K.
Summary: Vitiligo affects around 1% of the world's population. Despite it being relatively common, there is still no effective treatment. The objective of this study was to update the Cochrane systematic review of randomized clinical trials (RCTs) to evaluate the efficacy of treatments for vitiligo. We carried out searches of a range of databases to October 2013 for RCTs of interventions for vitiligo regardless of language or publication status. At least two reviewers independently assessed study eligibility and methodological quality and extracted data using data extraction forms approved by the Cochrane Skin Group. Our primary outcomes of interest were quality of life, > 75% repigmentation and adverse effects. We retrieved 96 studies, of which 39 were new studies, with an overall total of 4512 participants. Repigmentation was assessed in all studies, although only five reported on all three of our primary outcomes. Regarding our two secondary outcomes, six studies measured cessation of spread but none assessed long‐term permanence of repigmentation at 2 years' follow‐up. Most of the studies evaluated combination treatments, which generally showed better repigmentation than monotherapies. Of the new studies, seven were surgical interventions. The majority of the studies had fewer than 50 participants. The quality of the studies was poor to moderate at best. Very few studies specifically included children or participants with segmental vitiligo. Five years after the last update of this review, there are still important variations in study design and outcome measures in clinical trials for vitiligo, limiting the evidence for the efficacy of different therapeutic options. The best evidence from individual trials showed short‐term benefit from topical corticosteroids and various forms of ultraviolet radiation combined with topical preparations. Long‐term follow‐up and patient‐rated outcomes should be incorporated into study design, and more studies should assess psychological interventions. Abstract : What's already known about this topic? Vitiligo is a skin disease with limited treatment options. Most of the published vitiligo clinical trials are of poor methodological quality. What does this study add? There are still important variations in study design and outcome measures in vitiligo clinical trials. Individual trials showed short‐term benefit from topical corticosteroids and various forms of ultraviolet combined with topical preparations. Long‐term follow‐up and patient‐rated outcomes should be incorporated into study design, and more studies should assess psychological interventions.